KEY ISSUES AND RESEARCH AREAS IN DISCOURSE ANALYSIS: A METHODOLOGICAL FRAMEWORK - Mahamdeh, Ahmad; Hawamdeh, Mohammad; Al Aqqad, Mohammad (Universitas Islam Negeri Sunan Gunung Djati, 2025)
This study examines the methodical frameworks in textual, political, and critical discourse analysis by three case studies: the continuity of sense in wartime, local coherence in political communiqué and formal properties of literary language. As master’s theses defended at Jerash University, Jordan in 2022/2023.These master’s theses sought to handle the key issues in the related studies. They also evaluated the efficacy of the corpus - based approaches in analyzing discursive phenomena and in real-world language patterns to understand how context influences meaning. The study utilizes a qualitative case-study method to explore essential subjects in DA along with their sampling frames and instrumental designs. By examining of linguistic corpora from such fields as literature, politics and intercultural debates, the efficacy of well-structured methods in enabling detailed analyses and revealing new insights is illustrated. Zelensky’s (2022) Addresses in Ukraine’s Crisis, Obama’s (2020) A Promised Land and Hosseini’s (2007) A Thousand Splendid Suns represent these research areas. The results emphasize the potential of corpus-based methods to provide crucial insights and vital resources for persuasion, diplomacy and interpretation, carrying values for related areas like translation studies, semiotics, political communication and pragmatics.